Madrasah Principal Change Management in Creating a Superior Madrasah - Alfiah, Levi Nur; Yahya, Fata Asyrofi; Ratnawati, Siti Rohmaturrosyidah; Bueraheng, Ibroheng (Program Studi Pendidikan Agama Islam, 2023)
This research aims to identify the madrasa head's strategy for managing change in creating superior madrasas and to analyze the success of change management in creating superior madrasas. The research method used is descriptive qualitative with data collection through observation, interviews, and documentation. The results of the study indicate that the implementation of change management in madrasahs, especially Madrasah Aliyah (MA) needs to be implemented and the principal plays a key role in the success of leading change in realizing superior madrasahs by implementing change management, including Awareness, namely motivation and monthly meetings; Desire, namely a personal approach and giving rewards; Knowledge, namely discussion and socialization activities; Ability, namely workshop activities; and Reinforcement, namely monitoring and controlling. Indicators of superior madrasahs include Input, namely the acceptance of new students; Process, namely teacher abilities, learning facilities, curriculum, learning methods, extracurricular activities, and cooperation networks; and Output, namely intellectual competence, emotional competence, and spiritual competence.